Panorama do esporte em Manaus - 1897 a 1911 - Eliza Salgado de Souza (2017)
This study aimed to investigate and describe the organization of sports in the city of Manaus in the late 19th and early 20th centuries. For both, took as its starting point the foundation of a sport club, the Sport Club of Amazonas, in 1897, delimiting the clipping temporal until 1911, when it stops the operation of the Prado Amazonense, important place of realization and appreciation of the turf in the city, and there is an intensification of the organization of football. To accomplish the research were consulted periodicals of the time available in the Hemeroteca Digital. During this period Manaus became an important center importer and exporter, undergone many transformations that led to structural changes and social. In the midst of this spectrum sports clubs and places for the practice of sports, become part of the possibilities of sociability of the city. The principle are two clubs, Sport Club of Amazonas and the Group Cyclista Amazonense. The first by the practice of sports and parties and the second by organizing tours and races through the city. However, with the turn of the 20th century, new clubs are founded and built spaces specifically for the consideration and practice of sports, the Velódromo Amazonense, site of racing bike and the meadow of Amazonas, site of horse racing.